The Relationship Between Transformational Leadership and Work Motivation to Organizational Commitment (Survey on the Bank Tabungan Negara) - Sagita Natalia, Putri; Wahyudin Suwandi, Yudi (Yayasan Pendidikan Belajar Berdikari, 2025)
This study aims to investigate the influence of transformational leadership and work motivation on organizational commitment at the Bank Tabungan Negara. Employee performance that is not optimal due to suboptimal organizational commitment which is influenced by suboptimal transformational leadership is not yet effective and work motivation is not optimal. The data collection of this study used a survey by distributing questionnaires to 172 respondents of Bank Tabungan Negara employees, The results of the study descriptively show that the condition of transformational leadership on the criteria is quite good to very good, work motivation on the criteria is quite good to good, organizational commitment on the criteria is quite good to very good and employee performance on the criteria is quite good to very good. The results of the research by verifying show that transformational leadership and work motivation have a positive and significant influence partially and simultaneously on organizational commitmen